Introduction to Relativity - Narlikar, Jayant V. (Delhi: Cambridge University Press, 2010)
General relativity is now an essential part of undergraduate and graduate courses in physics, astrophysics and applied mathematics. This simple, user-friendly introduction to relativity is ideal for a first course in the subject. Beginning with a comprehensive but simple review of special relativity, the book creates a framework from which to launch the ideas of general relativity. After describing the basic theory, it moves on to describe important applications to astrophysics, black hole physics, and cosmology. Several worked examples, and numerous figures and images, help students appreciate the underlying concepts. There are also 180 exercises which test and develop students` understanding of the subject. The textbook presents all the necessary information and discussion for an elementary approach to relativity.
References 353-352p.; Index 358-363p.
Keywords: Beyond relativity; Einsteins equations; Relativistic astrophysics; Covariant differentiation